KHI Versus CLD KHI: Studi Kasus pada Implementasi di Indonesia - Tedi Sumaelan (Universitas Darunnajah Jakarta, Indonesia, 2024)
This study aims to examine the differences in epistemology, orientation, and substance between the Compilation of Islamic Law (KHI) and the Counter Legal Draft Compilation of Islamic Law (CLD KHI) as products of Islamic family law reform in Indonesia, as well as socio-political factors that influence the codification and implementation process of both. This research uses a qualitative method with a case study approach. Data were collected through document studies, interviews, and observations. The results show that KHI and CLD KHI have differences in epistemology, orientation, and substance that reflect different views on Islamic law and women. KHI is more conservative, formalistic, and patriarchal, while CLD KHI is more progressive, substantial, and egalitarian. Socio-political factors that influence the codification and implementation process of both include political context, social power, and intellectual dynamics. This research provides implications and recommendations for the development of Islamic family law that is more just, democratic, and responsive to the needs of society.